Clinical Characteristics of Immune Response in Asymptomatic Carriers and Symptomatic Patients With COVID-19 - Li, Entao; Wang, Shen; He, Wenwen; He, Jun; Liu, Luogeng; Zhang, Xiaotuan; Yang, Songtao; Yan, Feihu; Gao, Yuwei; Liu, Bin; Xia, Xianzhu (Frontiers in Microbiology, 2022)
The pandemic of coronavirus disease 2019 (COVID-19) has emerged as a major public health challenge worldwide. A comprehensive understanding of clinical characteristics and immune responses in COVID-19 asymptomatic carriers and symptomatic patients is of great significance to the countermeasures of COVID-19 patients. Herein, we described the clinical information and laboratory findings of 43 individuals from Hunan Province, China, including 13 COVID-19 asymptomatic carriers, 10 symptomatic patients as well as 20 healthy controls from January 25 to May 18, 2020. The serum samples of these individuals were analyzed to measure the cytokine responses, receptor binding domain (RBD) and Nucleocapsid (N) protein-specific antibody titers as well as SARS-CoV-2 neutralizing antibodies (nAbs). For cytokines, significantly higher Th1 cytokines including IL-2, IL-8, IL-12p70, IFN-γ and TNF-α as well as Th2 cytokines including IL-10 and IL-13 were observed in symptomatic patients compared with asymptomatic carriers. Compared with symptomatic patients, higher N-specific IgG4/IgG1 ratio and RBD-specific/N-specific IgG1 ratio were observed in asymptomatic carriers. Comparable nAbs were detected in both asymptomatic carriers and symptomatic COVID-19 patients. In the symptomatic group, nAbs in patients with underlying diseases were weaker than those of patients without underlying diseases. Our retrospective study will enrich and verify the clinical characteristics and serology diversities in COVID-19 asymptomatic carriers and symptomatic patients.